2013
DOI: 10.1186/2196-1042-14-32
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional methodology for photogrammetric acquisition of the soft tissues of the face: a new clinical-instrumental protocol

Abstract: BackgroundThe objective of this study is to define an acquisition protocol that is clear, precise, repeatable, simple, fast and that is useful for analysis of the anthropometric characteristics of the soft tissue of the face.MethodsThe analysis was carried out according to a new clinical-instrumental protocol that comprises four distinct phases: (1) setup of portable equipment in the space in which field analysis will be performed, (2) preparation of the subject and spatial positioning, (3) scanning of the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…A previous study on the 3D images of the Miss Italy 2010 contestants showed that their facial width was 83.5 mm at the inter-exocanthus and 73.7 mm at the inter-gonion 38. However, in the MK group of our study, the corresponding facial widths were 95.7 mm and 119.1 mm, respectively.…”
Section: Discussioncontrasting
confidence: 77%
“…A previous study on the 3D images of the Miss Italy 2010 contestants showed that their facial width was 83.5 mm at the inter-exocanthus and 73.7 mm at the inter-gonion 38. However, in the MK group of our study, the corresponding facial widths were 95.7 mm and 119.1 mm, respectively.…”
Section: Discussioncontrasting
confidence: 77%
“…A surface electromyographic electrode (T3402M, Thought Technology Ltd., Montreal, Canada) was attached to the forehead, serving as a fiducial marker for subsequent image registration. Markings were placed on participants' lips using hypoallergenic pencil makeup 17 to facilitate identification of anatomical landmarks during image analysis ( Figure 1). Participants were then asked to look straight at a screen positioned at their eye height in natural head position, maintain a neutral facial expression, and keep posterior teeth in slight contact with lips relaxed.…”
Section: Stereophotogrammetrymentioning
confidence: 99%
“…[ 14 15 16 ] In the recent times, noninvasive 3D scanning has become more popular and reliable method of analyzing craniofacial complex. [ 14 15 16 17 18 19 20 ]…”
Section: Introductionmentioning
confidence: 99%